30-Day Postoperative Morbidity and Readmission Following Revision Anterior Cervical Discectomy and Fusion (ACDF). Issue 10 (December 2019) - Malik, Azeem T.; Khan, Safdar N.; Kim, Jeffery; Yu, Elizabeth
Abstract : Study Design: This was a retrospective cohort study. Objective: To analyze risk factors associated with 30-day adverse outcomes and readmissions after revision anterior cervical discectomy and fusion (ACDF). Summary of Background Data: No current literature has evaluated the risk factors associated with adverse outcomes after revision ACDF. Methods: The 2012–2016 American College of Surgeons-National Surgical Quality Improvement Program (ACS-NSQIP) database was queried using Current Procedural Terminology codes for ACDF (22551, 22554, and 63075) combined with Current Procedural Terminology codes 22830 (exploration of spinal fusion) or 22855 (removal of anterior instrumentation) to identify revision cases. Patients undergoing concurrent posterior cervical spine surgery and/or corpectomies were excluded from the analysis. A total of 1140 patients were retrieved for analysis. Results: Out of a total of 1140 patients, 51 (4.5%) experienced at least 1 any adverse event, with 40 (3.5%) experiencing a severe adverse event, and 17 (1.5%) experiencing a minor adverse event. A 30-day readmission rate was 3.4% (N=39) after a revision ACDF. On multivariate analysis, any adverse events were significantly associated with male sex [odds ratio (OR), 1.98], 2-level versus 1-level fusion (OR, 2.05), and a length of stay (LOS)>1 day (OR, 7.70). Severe adverse events were independently associated with male sex (OR, 2.85), smoking (OR, 0.33), 2-level versus 1-level fusion (OR, 2.03), and LOS>1 day (OR, 7.28). LOS>1 day was the only significant factor associated with an minor adverse event (OR, 14.65) and readmission within 30 days (OR, 2.67). Conclusions: Using a national surgical database, the study is the first of its kind to report rates and risk factors associated with adverse outcomes after ACDFs. Providers should understand the need of preoperative risk stratification in these patients to reduce the risk of experiencing adverse outcomes. Level of Evidence: Level III—retrospective.